Low genetic polymorphism of merozoite surface proteins 7 and 10 in Colombian Plasmodium vivax isolates (2011)
The merozoite surface protein (MSP) family is involved in the initial interaction between merozoites and erythrocytes in Plasmodium species, its members are therefore becoming major targets for vaccine development. Considering that antigens included in a subunit malaria vaccine should be both accessible to the immune system and lack genetic diversity or have very limited polymorphism, we have analyzed the genetic diversity of three msp genes (msp-7A, msp-7K and msp-10) in different geographical regions of Colombia. The results showed that these genes follow the neutral model of evolution and also display low genetic diversity. The strong conservation found for msp-7 haplotypes in isolates from geographically different regions further suggests that these proteins could be good components of a vaccine against Plasmodium vivax malaria, thereby avoiding strain-specific immune responses. © 2010 Elsevier B.V.